2016
DOI: 10.1016/j.beproc.2015.11.007
|View full text |Cite
|
Sign up to set email alerts
|

The effect of the amount of blocking cue training on blocking of appetitive conditioning in mice

Abstract: HighlightsBlocking of appetitive conditioning in mice has rarely been demonstrated.Blocking occurred when there was 200, but not 80 trials with a visual blocking cue.Blocking occurred independent of trial number with an auditory blocking cue.Post-asymptotic training is necessary under certain conditions for blocking.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
11
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 30 publications
2
11
0
Order By: Relevance
“…Figure 11 shows the CR of the final phase of learning in the intact system; which presented the blocking effect due to the prior conditioning in the preceding phases, as confirmed experimentally by [ 38 , 39 , 40 ]. The blocking effect can be eliminated by extending the conditioning of the second phase, which made it longer, as shown in Figure 12 and confirmed experimentally by [ 38 , 41 , 42 ]. Although lesioning the CHCQ model did not affect the output CR, as shown in Figure 13 , this is supported by the experimental findings of [ 43 , 44 , 45 ].…”
Section: Resultssupporting
confidence: 54%
“…Figure 11 shows the CR of the final phase of learning in the intact system; which presented the blocking effect due to the prior conditioning in the preceding phases, as confirmed experimentally by [ 38 , 39 , 40 ]. The blocking effect can be eliminated by extending the conditioning of the second phase, which made it longer, as shown in Figure 12 and confirmed experimentally by [ 38 , 41 , 42 ]. Although lesioning the CHCQ model did not affect the output CR, as shown in Figure 13 , this is supported by the experimental findings of [ 43 , 44 , 45 ].…”
Section: Resultssupporting
confidence: 54%
“…Within the field of associative learning more generally, a recent response by Soto (2018) to a study investigating the replicability of blocking in Pavlovian conditioning in rats (Maes et al, 2016) argued that a number of existing models of associative learning anticipate the parameters that are likely to lead to a failure of blocking (Kinder & Lachnit, 2003;Soto, Gershman, & Niv, 2014;Wagner, 2003), and are able to predict the failures of blocking reported by Maes et al (2016). Sanderson, Jones, & Austen (2016) recently examined the parameters that promote the detection of blocking in mice, such as cue salience and the extent of phase 1 conditioning, but more systematic studies of this kind are necessary. In relation to studies on incidental spatial learning, there is a clear need for experiments that do not rely on an absence of evidence to support the existence of distinct learning mechanisms, and in particular any claims of incidental learning of cues.…”
Section: Discussionmentioning
confidence: 99%
“…This indirect way of assessing learning may be less prone to ceiling and floor effects that may occur. Indeed, we have previously found that cues that elicit similar levels of conditioned responding may result in different levels of blocking ( Sanderson et al, 2016 ). A potential disadvantage of this method, however, is that cue competition effects may be mediated by the strength of within-compound associations between the competing cues ( Blaisdell et al, 1999 ).…”
Section: Discussionmentioning
confidence: 99%
“…The modality of the 10-s cue was also included as a nuisance factor. We have previously found that mice respond more to auditory cues than visual cues ( Sanderson et al, 2016 ). Therefore, the variance caused by this counterbalancing factor was controlled by including it in the ANOVA, but the main effect of modality and any interactions that included modality were ignored.…”
Section: Methodsmentioning
confidence: 99%